Generation mean analysis of horticultural traits in mid‐late cauliflower (Brassica oleracea L. var. botrytis) under sub temperate conditions of Western Himalayas. (4th January 2018) - Verma, Arti; Singh, Yudhvir
Abstract: Suitable breeding procedure for crop improvement mainly depends on the type and relative amount of genetic components and presence of non‐allelic interactions. Therefore, the study was carried out during three successive rabi seasons 2013‐14, 2014‐15 and 2015‐16 in mid hill zone of North‐western Himalayas, India with objective to estimate the main genetic effects including digenic non‐allelic interactions controlling horticultural traits in cauliflower. The generation mean analysis was carried out on six generations (P1, P2, F1, F2, B1 and B2 ) of six crosses involving four diverse parents of cauliflower. The results obtained revealed that the nature and magnitude of gene effects differed in different crosses and showed importance of duplicate epistasis in the inheritance of curd diameter and curd size index, whose effect can be wiped out by following sophisticated selection procedure such as reciprocal recurrent selection and/or biparental mating in early segregating generation. Complementary type of epistasis was recorded in most of the cross combinations for the important yield traits, which indicates the importance of heterosis breeding for the development of high yielding varieties.